Factors Affecting Patient Safety in Independent Midwifery Practice - Mozha Desri Puji Astuti; Yudhy Dharmawan; Daru Lestantyo; Nurjazuli Nurjazuli (PSPP JOURNALS, 2026)
This study aims to analyze the factors influencing the achievement of patient safety goals in independent midwifery practice, focusing on the roles of knowledge, attitude, practice, and motivation, as well as the mediating effect of motivation. Patient safety is a critical aspect of healthcare services, and midwives play a vital role in its implementation. Using a quantitative approach, this research involved 163 respondents consisting of independent midwives and pregnant women in Tangerang Regency. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results showed that knowledge did not have a significant direct effect on patient safety goals, while attitude and practice significantly influenced their achievement, with practice being the most dominant factor. Motivation also did not directly affect patient safety goals but was found to significantly mediate the relationship between knowledge and practice on patient safety goals, while it did not mediate the effect of attitude. Based on these findings, it is recommended that future research explores additional variables such as organizational support and workload, applies longitudinal and qualitative approaches, and expands the study area to provide a more comprehensive understanding of factors affecting patient safety in independent midwifery practice.